2021
DOI: 10.1136/jitc-2021-002876
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral injection of TLR9 agonist promotes an immunopermissive microenvironment transition and causes cooperative antitumor activity in combination with anti-PD1 in pancreatic cancer

Abstract: BackgroundComplex tumor and immune microenvironment render pancreatic ductal adenocarcinoma (PDAC) resistant to immune checkpoint inhibitors (ICIs). Therefore, a strategy to convert the immune hostile into an immunopermissive tumor is required. Recent studies showed that intratumoral injection of Toll-like receptor 9 agonist IMO-2125 primes the adaptive immune response. Phase I and II trials with intratumoral IMO-2125 demonstrated its safety and antitumoral activity.MethodsWe generated an array of preclinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…The combination of Vidutolimod (formerly CMP-001) and pembrolizumab (PD-1 Ab) entered Phase Ib clinical studies to cure patients with advanced melanoma, in which 25% of patients experienced tumour regression (including non-intratumoral injected tumours) [65]. The synergistic effect of TLR9 agonists cooperating with anti-PD-1 also has been validated in multiple mouse tumour models, including pancreatic ductal adenocarcinoma (PDAC) [66], lung cancer [67], breast cancer [68], colorectal cancer [69] and lymphoma [70]. In immunogenic B16/OVA melanoma, the combination of CpG1826 with anti-CTLA-4 resulted in bilateral tumour reduction, which was associated with increased tumour-antigen-specific T cell infiltration and decreased Tregs and inflammatory cytokines [71].…”
Section: Tlr9 and Immune Checkpoint Inhibitor (Ici) Combination Thera...mentioning
confidence: 99%
“…The combination of Vidutolimod (formerly CMP-001) and pembrolizumab (PD-1 Ab) entered Phase Ib clinical studies to cure patients with advanced melanoma, in which 25% of patients experienced tumour regression (including non-intratumoral injected tumours) [65]. The synergistic effect of TLR9 agonists cooperating with anti-PD-1 also has been validated in multiple mouse tumour models, including pancreatic ductal adenocarcinoma (PDAC) [66], lung cancer [67], breast cancer [68], colorectal cancer [69] and lymphoma [70]. In immunogenic B16/OVA melanoma, the combination of CpG1826 with anti-CTLA-4 resulted in bilateral tumour reduction, which was associated with increased tumour-antigen-specific T cell infiltration and decreased Tregs and inflammatory cytokines [71].…”
Section: Tlr9 and Immune Checkpoint Inhibitor (Ici) Combination Thera...mentioning
confidence: 99%
“…Carbone et al. ( 185 ) showed that intratumoral injection of the Toll-like receptor 9 agonist IMO-2125 in combination with anti-PD1 activated an immune-suppressive to immune-permissive transition of the TME in PDAC models with both high and low immunogenic potential. Toll-like receptor 9 (TLR-9) is a pattern recognition receptor that is predominantly located in the cytoplasm of DCs, macrophages, NK cells, and other APCs.…”
Section: Therapeutic Strategies: How Can We Harness Our Knowledge Abo...mentioning
confidence: 99%
“…Cells were daily inspected and routinely tested to be mycoplasma free by PCR assay. We characterized these models in a previous paper [34]( 10.1136/jitc-2021-002876) for both transcriptome and immune pro ling. From these cell lines we also established 3D cultures 13KC (DT4313), KPC06 (FC1242), KPC12 (FC1245).…”
Section: Pdac Murine Cell Lines and 3d Culturesmentioning
confidence: 99%